Analysis of the volume of fluid (VOF) method for the simulation of the mucus clearance process with CFD. Issue 5 (4th April 2019) - Paz, Concepción; Suárez, Eduardo; Vence, Jesús; Cabarcos, Adrián
Abstract: The clearance of mucus through coughing is a complex, multiphase process, which is affected principally by mucus viscosity and airflow velocity; however, it is also critically affected by the thickness of the two layers of mucus—the serous and gel layers—and oscillation level. The present study examines the effects of the latter parameters more closely. To do so, the mucus clearance process is simulated with a transient 3D volume of fluid (VOF) multiphase model in ANSYS Fluent. The model includes mucus' bilayer properties and a wide range of boundary conditions were tested. The model was analysed in both a straight tube and a realistic trachea. Ultimately, the model was able to both capture air-mucus interface wave evolution and predict the overall behaviour of the clearance process. The results were consistent with experimental clearance data and numerical airflow simulations, which indicates our methodology is appropriate for future studies. Ultimately, the mere presence of the serous layer was found to increase mucus clearance by more than 15 percent. An oscillating flow enhanced clearance by up to 5 percent. Interestingly, interface wave steepness was found to be inversely correlated with mucus thickness, but directly with mucus velocity, which suggests it will be an interesting parameter for further study.